2014
DOI: 10.1063/1.4860976
|View full text |Cite
|
Sign up to set email alerts
|

Organization of polymer chains onto long, single-wall carbon nano-tubes: Effect of tube diameter and cooling method

Abstract: We use molecular dynamics simulations to investigate the arrangement of polymer chains when absorbed onto a long, single-wall carbon nano-tube (SWCNT). We study the conformation and organization of the polymer chains on the SWCNT and their dependence on the tube's diameter and the rate of cooling. We use two types of cooling processes: direct quenching and gradual cooling. The radial density distribution function and bond orientational order parameter are used to characterize the polymer chain structure near t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
0
11
1
Order By: Relevance
“…Besides the active force, our model is different from these studies: we don't consider the torsion energy in our polymer model and our cylindrical surface is smooth without the chiral arrangement of beads. Thus, we observed a helix-like conformation, which is, strictly speaking, not the helical conformation found by Tallury 38 and Kumar et al 39 It is like a state between non-helical loop 7 and helical conformation.…”
Section: Phase Diagramcontrasting
confidence: 85%
See 1 more Smart Citation
“…Besides the active force, our model is different from these studies: we don't consider the torsion energy in our polymer model and our cylindrical surface is smooth without the chiral arrangement of beads. Thus, we observed a helix-like conformation, which is, strictly speaking, not the helical conformation found by Tallury 38 and Kumar et al 39 It is like a state between non-helical loop 7 and helical conformation.…”
Section: Phase Diagramcontrasting
confidence: 85%
“…They found that the flexible polymer tends to wrap around the SWCNT without any distinct conformation while a semi-flexible polymer wraps around the tube in a helical conformation. Kumar et al 39 studied the arrangement of polymer chains on a long SWCNT and they found a lamellar configuration on the SWCNT of the smallest radius due to the smaller torsion energy penalty. In an equilibrium state, the conformation of the polymer results from the competition between elastic energy and entropy.…”
Section: Phase Diagrammentioning
confidence: 99%
“…In addition, to further confirm the flexibility of P8BT and PDFP molecular chains, Equation is used to define the radius of gyration, Rg trueRg2=1Ni=1N(ri-rcm)2 …”
Section: Resultsmentioning
confidence: 99%
“…The Nose-Hoover thermostat [44,45] was implemented to control the desired temperature of the system along with the velocity-Verlet algorith m [46] with a time step of 1 fs. The simulation temperature was decreased from 800 K to 300 K in the steps of 50 K. Simulations were run for 1000 ps at each temperature step during cooling as reported in our previous studies [47,48]. The values of all parameters for polymer nano-particle system were based on the DREID-ING [49] force field.…”
Section: Simulation Methodsmentioning
confidence: 99%